2022
DOI: 10.1039/d2dt02554j
|View full text |Cite
|
Sign up to set email alerts
|

A ferromagnetically coupled pseudo-calixarene [Co16] wheel that self-assembles as a tubular network of capsules

Abstract: Reaction of Co(OAc)2·4H2O and Hsal in a basic MeCN solution affords the hexadecanuclear wheel [Co16(sal)16(OAc)16]·16MeCN (1·16MeCN) that displays ferromagnetic nearest neighbour exchange and has pseudo-calixarene character. Symmetry equivalent wheels self-assemble...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…23 This methodology has been shown to reproduce experimental magnetic exchange interactions accurately. 24…”
Section: Methodsmentioning
confidence: 99%
“…23 This methodology has been shown to reproduce experimental magnetic exchange interactions accurately. 24…”
Section: Methodsmentioning
confidence: 99%
“…27 Milios et al synthesized Co 16 by salicylaldehyde bridges. 28 Besides, Baca et al constructed a heterometallic ring Fe 6 Dy 8 with N -butyl diethanolamine isobutyrate and methanol (O hydroxyl ). 29 Yamamoto et al reported a series of [Pt(μ-SC 8 H 17 ) 2 ] n ( n = 5–13) clusters with the S atom as the connection point.…”
Section: Introductionmentioning
confidence: 99%